Comparative Study On Dry And Wet Sliding Friction And Wear Performance Of Commercial And Non-Commercial Brake Pad Materials - Liew, Kia Wai (2008)
The wet friction and wear results revealed that regardless the wear rate, the highest friction coefficient was consistently exhibited by NF2 at all pressure and speeds whereas the lowest wet friction coefficient was obtained by NF1.